2020
DOI: 10.1016/j.euroneuro.2020.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Sigma-1 (σ1) receptor activity is necessary for physiological brain plasticity in mice

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…In addition to 5-HT 2A receptors, the effects on neurogenesis seen with DMT and 5-MeO-DMT could potentially involve other receptors [ 42 , 43 ]. DMT has low but functionally significant affinity for the sigma-1 receptor, an orphan receptor involved in neuroprotection and neurogenesis [ 78 ]. Sigma-1 receptor antagonists block DMT’s effects on hippocampal neurogenesis [ 44 , 79 ], and sigma-1 receptor activity has also been shown to stimulate neurogenesis in previous studies [ 80 – 82 ].…”
Section: How Do Psychedelics Enhance Neuroplasticity?mentioning
confidence: 99%
“…In addition to 5-HT 2A receptors, the effects on neurogenesis seen with DMT and 5-MeO-DMT could potentially involve other receptors [ 42 , 43 ]. DMT has low but functionally significant affinity for the sigma-1 receptor, an orphan receptor involved in neuroprotection and neurogenesis [ 78 ]. Sigma-1 receptor antagonists block DMT’s effects on hippocampal neurogenesis [ 44 , 79 ], and sigma-1 receptor activity has also been shown to stimulate neurogenesis in previous studies [ 80 – 82 ].…”
Section: How Do Psychedelics Enhance Neuroplasticity?mentioning
confidence: 99%
“…The two compounds stand out as candidates for interrogating previously proposed interplay between 5-HT and σ receptors to induce neuroplasticity. 38,39 While both drug molecules reveal comparable affinities at σ receptors, 4-HO-NBnT distinctively exhibits high affinity and activity at 5-HT receptors, while 4-HO-NcHT does not. This suggests a congruent binding modality for both compounds at σ receptors, while differing substantially in their interactions at 5-HT receptors.…”
Section: Head Twitch Response Studiesmentioning
confidence: 99%
“…On the other hand, sigma-1 knockout male and female mice had impaired long-term, but not short-term, recognition memory ( Xu et al, 2017 ). Also, the Hamlet test, where animals are exposed to an enriched environment, showed that lack of sigma-1 receptors completely prevented the establishment of topographic memory and behavioral resilience, as well as the hippocampal neurogenesis ( Crouzier et al, 2020 ). These differences between males and females suggest that sex hormones may affect sigma-1 receptors signaling and in consequence memory processes.…”
Section: Memory Functioning and Sigma-1 Receptorsmentioning
confidence: 99%